Association between nutritional status and children and adolescents' dental caries experiences: an overview of systematic reviews - Thaís de Oliveira FERNANDES; Patrícia Arriaga CARVALHO; Fernanda Volpe de ABREU; Christian KIRSCHNECK; Erika Calvano KÜCHLER; Leonardo Santos ANTUNES; Lívia Azeredo Alves ANTUNES (University of São Paulo, 2023)
Abstract An increasing number of systematic reviews (SR) has investigated the association between dental caries and nutritional status in children and adolescents, thus requiring an overview to compile the information in a single piece of evidence. Therefore, this study aimed to evaluate and summarize evidence from published SR on the association between dental caries and nutritional status in children and adolescents. A wide search was conducted on May 29, 2023, in six databases (Medline via PubMed, Scopus, Web of Science, Cochrane library, Embase, and the Virtual Health Library - VHL). An additional search was performed in the gray literature (Open grey and Google Scholar), SR registration databases, and the list of references of the included SR. Our inclusion criteria were based on acronym PECOS. Overall, two reviewers independently extracted the data, evaluated the risk of bias (ROBIS), and assessed the quality of the chosen studies (AMSTAR-2). Data from the included meta-analysis were summarized and certainty of evidence using the GRADE approach was performed. After removing duplicates and applying our eligibility criteria, 19 SR from 2006-2022 were included. We found that 17 SR showed high risk of bias and critically low methodological quality. We observed an association between dental caries experiences and nutritional status since seven SR found an association between obesity/overweight and dental caries; one, an association between underweight and dental caries; and eleven, no associations. The meta-analysis showed divergent results according to the study designs, used indices, and participants' age group, and were scored as having a very low certainty of evidence. Therefore, based on the high risk of bias, low methodological quality, and very low certainty of evidence of the chosen SR, most studies found no association between children and adolescents' nutritional status and dental caries experience.